TOXICITY OF INSECTICIDAL PRINCIPLES FROM CASSAVA (MANIHOT ESCULENTA CRANTZ) ON PSEUDOSTEM WEEVIL (ODOIPOROUS LONGICOLLIS OLIVER) (COLEOPTERA: CURCULIONIDAE) IN BANANA - Krishnan, Jithu Unni; C. A., Jayaprakas; N.R., Lekshmi; L. S., Rajeshwari; S., Leena (JOURNAL OF ROOT CROPS, 2016)
ABSTRACT Injudicious use of chemical inputs in agriculture poses challenge to sustainable agriculture. Cassava (ManihotesculentaCrantz) is a climate resilient crop cultivated in tropical and subtropical countries for its tuber as food, feed, and industrial products. Nevertheless, owing to the presence of cyanoglucosides, leaves and tuber rinds are often thrown as waste or rather underutilized. The insecticidal principles from such biowastewere isolated (Pending patent) and made a formulation named Menma for the management of important borer pests of fruit and tree crops. Pseudostem weevil (BPW), Odoiporuslongicollis Oliver, a noxious pest of banana causes 100% yield loss due to premature cropfalling. The current management strategy relies upon application of very toxic synthetic insecticides;neverthelessno satisfactory control of the pest could be achieved. An extensive field study revealed that the infestation by BPW normally occurs from fifth month onwards in conjunction with the emergence of banana inflorescence. Management of this noxious pest was achieved using the two formulations as prophylactic and curative measures. Doses and application strategies of the bioformulations have been standardised bylarge-scale validation at the farmers’ fields in three districts of Kerala viz. Thiruvananthapuram, Malappuram and Kasaragod, and their potency in the management of the dreaded pest was established.